MANAGEMENT ACCOUNTING SYSTEMS AND MANAGERIAL SUPPORT INFLUENCE SUSTAINABLE MANUFACTURING SME PERFORMANCE THROUGH DIGITAL TRANSFORMATION MECHANISMS - Rizqi, Reza Muhammad; Akbar, Arya Zulfikar; Norzihad, Fatin Nabilah (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2026)
Purpose - Grounded in the Resource-Based View and Dynamic Capabilities Theory, this study investigates how digital transformation mediates the sustainable performance of Indonesian manufacturing SMEs. It evaluates the impact of environmental management accounting (EMA), innovative accounting instruments, and top management support on sustainability through digitalization. Methods - Utilizing a quantitative explanatory framework, data from 210 purposively selected SME managers were analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM), assessing mediation through the Variance Accounted For (VAF) approach. Findings - Results substantiate all proposed hypotheses. EMA, advanced instruments, and executive backing significantly propel digital transformation, elevating sustainable performance. Digital transformation operates as a partial mediator, yielding VAF values of 38.3%, 37.7%, and 39.3%. Research implications - While digitalization amplifies sustainability, managerial interventions remain indispensable. This study provides strategic insights for policymakers to synchronize modern accounting frameworks and leadership commitment with digital advancements. Originality - This research offers empirical value by quantifying the specific mediating role of digital transformation, proving how integrating technological capabilities and managerial resources actively fosters sustainable competitiveness in emerging-market manufacturing SMEs.